2020
DOI: 10.3390/molecules25030462
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid Saponin and Lignan Glycosides from the Traditional Medicine Elaeagnus angustifolia Flowers and Their Cytotoxic Activities

Abstract: A new triterpenoid saponin, named terpengustifol A (1), and two new lignan glucosides, phengustifols A and B (2 and 3), were isolated from the flowers of Elaeagnus angustifolia. Their structures were determined by the extensive analysis of the spectroscopic data (including NMR and HRMS) and ECD calculations. Compound 1 possesses an unusual monoterpene (Z)-6-hydroxy-2,6-dimethylocta-2,7-dienoyl unit at C-21. Compounds 2 and 3 are a pair of diastereoisomers, while their aglycones are a pair of enantiomers. Compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Of all the oils used in the study, only oleaster oil showed that the antiprotozoal effect increased linearly with increasing doses. According to Han et al (2020), the reason could be the presence of terpengustifol, a triterpenoid saponin. Many studies have shown that herbal saponins have potent antiprotozoal properties and can be used as a defaunating agent (Wallace, 2004;Guo et al, 2008;Hanim et al, 2009;Ramos-Morales et al, 2019;Tan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Of all the oils used in the study, only oleaster oil showed that the antiprotozoal effect increased linearly with increasing doses. According to Han et al (2020), the reason could be the presence of terpengustifol, a triterpenoid saponin. Many studies have shown that herbal saponins have potent antiprotozoal properties and can be used as a defaunating agent (Wallace, 2004;Guo et al, 2008;Hanim et al, 2009;Ramos-Morales et al, 2019;Tan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the spectral and physicochemical properties of these compounds ( Supplementary Materials ) with those of previously reported compounds, the sixteen compounds were identified as 4-hydroxybenzoic acid ( 1 ) [ 33 ], salicylic acid ( 2 ) [ 34 ], vanillic acid ( 3 ) [ 35 ], (+)-catechin ( 4 ) [ 36 ], (–)-epicatechin ( 5 ) [ 37 ], (+)-gallocatechin ( 6 ) [ 36 ], (–)-epigallocatechin ( 7 ) [ 38 ], procyanidin B3 ( 8 ) [ 39 ], procyanidin B4 ( 9 ) [ 40 ], kaempferol ( 10 ) [ 41 ], astragalin ( 11 ) [ 42 ], trans -tiliroside ( 12 ) [ 38 ], helichrysoside ( 13 ) [ 43 ], betulinic acid-3- O - trans -caffeate ( 14 ) [ 44 ], ursolic acid-3- O - trans -caffeate ( 15 ) [ 45 ], and 1-mono(22- O -feruloyl-oxydocosanoyl)glycerol ( 16 ) [ 46 ]. Previous studies have reported the presence of various types of phytochemicals in the genus Elaeagnus , including flavonoids (e.g., rutin, epigallocatechin gallate, and isorhamnetin) and phenolic compounds (e.g., chlorogenic acid, pyrogallol, and ferulic acid) from E. umbellata [ 20 ], E. angustifolia [ 47 ], and E. pungens [ 48 ]; and triterpenoid saponins (e.g., terpengustifol), lignan glycosides (e.g., phengustifols A and B), and alkaloids (e.g., harmane and tetrahydroharmol) from E. angustifolia [ 23 , 47 ]. Of note, this study represents for the first time these sixteen compounds have been identified in EGFOB.…”
Section: Resultsmentioning
confidence: 99%
“…glabra f. oxyphylla in a mouse model of scopolamine-induced memory impairment [ 22 ]. Previous studies have reported that the genus Elaeagnus contains flavonoids, triterpenoids, lignan glycosides, and phenolic compounds [ 17 , 20 , 23 ]. However, there have been no phytochemical studies using E. glabra f. oxyphylla extracts.…”
Section: Introductionmentioning
confidence: 99%
“…As a homologous variety, the flowers of Elaeagnus angustifolia L. (oleaster, Russian olive, or wild olive) have been used in the west zones of China [1][2][3][4]. Traditionally, the flowers were used as a medicine [5] for chronic bronchitis and tetanus [6], asthma [7][8][9], arthritis, and cough [10,11]. Additionally, it can also be used as a material of food additive for flavor treatment of some wines [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Torbati et al [7] utilized gas chromatography-mass spectrometry (GC-MS) for studying the compounds in the essential oil, and about 53 compounds can be quantified, including ethyl cinnamate, hexahydrofarnesyl acetone, palmitic acid, etc., which accounted for about 96.59% content in the essential oil. Chen et al [18] and Han et al [9] separated a number of new compounds in the flowers of E. angustifolia and characterized them by nuclear magnetic resonance (NMR), which involved macrocyclic flavonoid glycoside, triterpenoid saponin, and lignan glycosides [18]. Most of published works focused on the employment of GC-MS for characterizing the compounds in the flowers or related products [19].…”
Section: Introductionmentioning
confidence: 99%